Antarctic environments as models of planetary habitats: University Valley as a model for modern Mars and Lake Untersee as a model for Enceladus and ancient Mars. Issue 2 (3rd July 2017) - McKay, Christopher P.; Andersen, Dale; Davila, Alfonso
Abstract: The worlds in our Solar System of interest for the search for a second genesis of life are Mars, and oceans beneath the icy surfaces of the moons of the outer Solar System, in particular Enceladus. All of these worlds are extremely cold compared to the Earth. Thus, environments in the Antarctic represent useful analogues for studies of habitability in these other worlds, and research sites to develop strategies to search for life. Here we discuss two key analogue environments: permafrost soils in University Valley, a high elevation dry valley, as an analogue for modern Mars, and the perennially ice-covered Lake Untersee as an analogue for crater lakes on early Mars and subsurface oceans under ice. For Mars, the Antarctic analogues appear to discourage hope for life present on the surface today while also indicating that ice-covered lakes could have been a habitat for life over a more extensive period of Martian history than previously thought. For the ice-covered ocean worlds, the Antarctic analogues support the hypothesis that these habitats are suitable for microbial life. The study of Antarctic analogues provides a focusing of scientific approaches and a way to test ideas in advance of lengthy and expensive planetary missions.